Bulk Heterojunction Solar Cells: Insight into Ternary Blends from a Characterization of the Intermolecular Packing and Electronic Properties in the Corresponding Binary Blends. Issue 7 (8th June 2020) - Ashokan, Ajith; Wang, Tonghui; Coropceanu, Veaceslav; Brédas, Jean‐Luc
Abstract: While adding a third component to a binary blend in the active layer of an organic solar cell is a promising approach to improve device performance, the control of active‐layer morphology also becomes more complex. Here, a combination of molecular dynamics simulations and long‐range corrected density functional theory calculations is used to examine the intermolecular packing and electronic properties in two polymer donor/small‐molecule acceptor binary blends, D/A1 (donor/acceptor1) and D/A2 (donor/acceptor2), in order to gain insight into the D/A1/A2 ternary blend. The focus is on the blends of the 4‐(3‐(2‐decyltetradecyl)‐5′‐(2, 3‐difluoro‐4‐(5‐methylthiophen‐2‐yl)phenyl)‐[2, 2′‐bithiophen]‐5‐yl)‐7‐(4‐(2‐decyltetradecyl)‐5‐methylthiophen‐2‐yl)‐5, 6‐difluoro‐2‐propyl‐2H‐benzo[d][1, 2, 3]triazole (PTFB‐O) polymer donor with the 3, 9‐bis(2‐methylene‐(3‐(1, 1‐dicyanomethylene)‐indanone))‐5, 5, 11, 11‐tetrakis(5‐hexylthienyl)‐dithieno[2, 3‐d:2′, 3′‐d′]‐s‐indaceno[1, 2‐b:5, 6‐b′]dithiophene (ITIC‐Th) and 2, 2′‐((2Z, 2′Z)‐(((4, 4, 9, 9‐tetrakis(5‐hexylthiophen‐2‐yl)‐4, 9‐dihydro‐s‐indaceno[1, 2‐b:5, 6‐b′]dithiophene‐2, 7‐diyl)bis(4‐octylthiophene‐5, 2‐diyl))‐bis(methanylylidene))bis(3‐oxo‐2, 3‐dihydro‐1H‐indene‐2, 1‐diylidene))‐dimalononitrile (IEIC‐Th) acceptors. The intermolecular packings and extent of mixing between the polymer donor and the acceptor in both binary blends are found to be similar, which is consistent with the well‐mixed nature of the ITIC‐Th:IEIC‐Th phase and the quasi‐linear evolution of open‐circuit voltage as a function of ITIC‐Th concentration in the PTFB‐O:ITIC‐Th:IEIC‐Th ternary blend. The intermolecular packing patterns and electron‐transfer rates among the acceptors are explored to rationalize the higher electron mobility found in the PTFB‐O:ITIC‐Th blend. The energetic distribution of the charge‐transfer electronic states and non‐radiative recombination rates are also evaluated to understand the difference in voltage losses between the binary blends. Abstract : Adding a third component to a binary blend leads to more complex active‐layer morphology of an organic solar cell. Here, molecular dynamics simulations and long‐range corrected density functional theory calculations are combined to examine the intermolecular packing and electronic properties in two polymer donor/small‐molecule acceptor binary blends in order to gain insight into the corresponding ternary blend.